Pakistan : Staff Report for the 2004 Article IV Consultation, Ninth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2004)
This paper focuses on Pakistan's 2004 Article IV Consultation, Ninth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Request for Waiver of Performance Criteria (PCs). Implementation of the PRGF program in Pakistan remains broadly on track. All quantitative PCs and indicative targets for end-June 2004 were met. Structural reforms continue to be advancing, although four structural PCs were breached. A temporary intensification of an existing and the imposition of a new exchange restriction, however, were quickly reversed, and new tax exemptions have been offset by other tax measures.